PEMBELAJARAN TEKS NEGOSIASI BERMUATAN KEARIFAN LOKAL PADA SISWA KELAS X SMAN PAKUSARI - Yudha, Putri Adinda; Dzarna, Dzarna; Amilia, Fitri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to describe the implementation of negotiation text learning integrated with local wisdom among tenth-grade students at SMAN Pakusari. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Data analysis followed the interactive model proposed by Miles and Huberman, consisting of three main stages: data reduction, data display, and conclusion drawing. The results revealed that teachers incorporated local cultural contexts—such as community deliberations, traditional market transactions, and family interactions—into the negotiation text learning activities. This approach positively influenced students’ understanding, engagement, and character development by reinforcing cultural values such as politeness, mutual cooperation, and tolerance. Despite some challenges, including students' difficulties in distinguishing negotiation texts from other types and organizing complete text structures, the integration of local wisdom proved effective in enhancing the quality of Indonesian language learning. This research recommends the development of contextual teaching materials based on local culture to improve literacy while preserving cultural values in education.